Cost-effectiveness of direct-acting antiviral regimen ombitasvir/paritaprevir/ritonavir in treatment-naïve and treatment-experienced patients infected with chronic hepatitis C virus genotype 1b in Japan. (1st December 2016) - Virabhak, Suchin; Yasui, Kikuo; Yamazaki, Kiyotaka; Johnson, Scott; Mitchell, Dominic; Yuen, Cammy; Samp, Jennifer C.; Igarashi, Ataru
Abstract: Objective: This study compared the cost-effectiveness of chronic hepatitis C virus (HCV) genotype 1b (GT1b) therapy ombitasvir/paritaprevir/ritonavir (OBV/PTV/r) vs daclatasvir + asunaprevir (DCV/ASV) and no treatment in patients without cirrhosis. Cost-effectiveness analyses (CEAs) that compared OBV/PTV/r against DCV/ASV and sofosbuvir/ledipasvir (SOF/LDV) in Y93H mutation-negative, GT1b patients with and without cirrhosis were also included. Methods: A health state transition model was developed to capture the natural history of HCV. A CEA over a lifetime horizon was performed from the perspective of the public healthcare payer in Japan. Costs, health utilities, and rates of disease progression were derived from published studies. Sustained virologic response (SVR) rates of OBV/PTV/r and DCV/ASV were extracted from Japanese clinical trials. Analyses were performed for treatment-naïve and -experienced patients. Alternative scenarios and input parameter uncertainty on the results were tested. Results: OBV/PTV/r exhibited superior clinical outcomes vs comparators. For OBV/PTV/r, DCV/ASV, and no treatment, the lifetime risk of decompensated cirrhosis in treatment-naïve patients without cirrhosis was 0.4%, 1.4%, and 9.2%, and hepatocellular carcinoma was 6.5%, 11.4%, and 49.9%, respectively. Quality-adjusted life years (QALYs) were higher in treatment-naïve and -experienced patients without cirrhosis treated with OBV/PTV/r (16.41 and 16.22) vs DCV/ASV (15.83 and 15.66) or no treatment (11.34 and 11.23). In treatment-naïve and -experienced patients without cirrhosis, the incremental cost-effectiveness ratios (ICERs) of OBV/PTV/r vs DCV/ASV were JPY 1, 684, 751/QALY and JPY 1, 836, 596/QALY, respectively; OBV/PTV/r was dominant compared with no treatment. In scenario analysis, including GT1b patients with and without cirrhosis who were Y93H mutation-negative, the ICER of OBV/PTV/r vs DCV/ASV was below the Japanese willingness-to-pay threshold of JPY 5 million/QALY, while the ICER of SOF/LDV vs OBV/PTV/r was above this threshold; thus, OBV/PTV/r was cost-effective. Conclusion: OBV/PTV/r appears to be a cost-effective treatment for chronic HCV GT1b infection against DCV/ASV. OBV/PTV/r dominates no treatment in patients without cirrhosis.